ETHNOBOTANICAL NOTE ON THE VETERINARY HEALTH-CARE MANAGEMENT BY MALAYALI TRIBES OF KALRAYAN HILLS - M, Kannan; T, Senthil Kumar; Mv, Rao (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Livestock is considered as the wealth of the tribal people, and the tribes are having rich knowledge on ethno-veterinary (EV) health-care management. Keeping this in view, the study was carried out to document ethno-veterinary medicinal (EVM) knowledge of Malayali tribes, the native people of Kalrayan Hills, Salem, Tamil Nadu, to improve their socio-economic status. Methods: Ethnobotanical survey was carried out in Kalrayan hills for EVM practices through regular field visits to the various hamlets of the study area from December 2009 to December 2014. EVM information was collected through personal interviews, field observations, and discussions among the traditional healers having familiarity and knowledge on Ethnoveterinary Medicine [EVM]. Results: Utilization of 137 plant species as EVM, belonging to 120 genera under 54 families, has been recorded against 40 livestock ailments with 126 types of preparations. Plant parts, such as leaf, root, flower, bark, resin, and rhizome, are used in the preparation. Among the plant parts, bark is predominately used. Most of the preparations include parts of more than one plant as the ingredients, and many of such combined preparations are used for treating more than one ailment. Conclusion: In the present study, we observed the prevalence of different types of livestock ailments in the study area, and the tribal community is having much knowledge on EV health-care management which is an integral part of their day-to-day life. Keywords: Ethnobotany, Ethno-veterinary medicine, Livestock, Malayali tribes, Eastern Ghats, Kalrayan hills, Salem.